A colonel in the armored divisions : a memoir, 1941-1945 - Triplet, William S., 1900- (University of Missouri Press, 2001)
"In this memoir William S. Triplet continues the saga begun in his earlier book, A Youth in the Meuse-Argonne: A Memoir, 1917-1918. After serving in World War I, Triplet chose to become a career military man and entered West Point. Upon graduation in 1924, his assignments were routine - to regiments in the Southwest and in Panama or as an officer in charge of Reserve Officers' Training Corps units or of men sent to a tank school. All this changed, however, when a new war opened in Europe." "Through his annotations, Robert H. Ferrell provides the historical context for Triplet's experiences. Well written and completely absorbing, A Colonel in the Armored Divisions provides readers the rare opportunity to see firsthand what a real professional in the U.S. Army thought about America's preparation for and participation in the war against Germany and Japan."--Jacket.